(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This research aims to understand the disjointed letters that appear in the openings of some surahs of the Holy Qur’an, through the speaker’s intention and the addressee’s understanding of this intention, with what is called in pragmatics communicative intention, since these letters have sparked great controversy regarding their intrinsic structure, and what they indicate outside of them on the one hand, and on the other hand. Another aspect is in the various grammatical directions in the context of the surah, in terms of its relationship to the verses that follow it, and in telling the speaker about it, intending to choose a specific syntactic structure, from what the rules of grammar and language allow him, in order to convey it to the recipient, who in turn realizes this intention, and thus achieves understanding and comprehension.